A coevolutionary approach to organizational learning and competition in markets - Olavarrieta Soto, Sergio (Estudios de Administración, 1996)
This article seeks to integrate the ideas of organizational learning literature within a more global model, where learning emerges from a dynamic and evolutionary competitive process. This process also explains the existence of firm heterogeneity in terms of patterns and performance. The model considers firms as systems that learn from competition in the market, which is seen not only as a resource allocator, but also as a scenario for experimentation and learning. Some implications for future research and management practice are offered.